(untitled) (diségno, 2026)
This paper presents the results of an investigation into the use of graphic representation in the design of bridges and viaducts within the work of Silvano Zorzi, a central figure of the twentieth-century Italian School of Structural Engineering. The study was carried out within the framework of the SIXXI research project – XX Century Structural Engineering: the Italian Contribution (ERC Advanced Grant, PIs: Sergio Poretti, Tullia Iori). Its aim is to highlight the role of drawing as a means of making visible the internal logic of the designed structure and, in particular, the coherence between form, structural behaviour, and construction process. The analysis is based not only on the available literature but, above all, on documentation preserved in the Zorzi Archive at the Politecnico di Milano and in numerous other archives belonging to clients and construction firms. Through these materials, the essay investigates how Zorzi, as a structural designer, employed representation –from the preliminary sketch to the executive detail– not only as a critical tool for control, used to describe and validate technical solutions, but also as a means of expressing the logic, at once rational and aesthetic, that governs structural form.